Shear fractures of the capitellum in children: a case report and narrative review - Pilotto, Jean-Marc; Valisena, Silvia; De Marco, Giacomo; Vazquez, Oscar; De Rosa, Vincenzo; Mendoza Sagaon, Mario; De Coulon, Geraldo; Dayer, Romain; Ceroni, Dimitri; Steiger, Christina (Frontiers in Surgery, 2024)
The shear fractures of the capitellum are rare fractures in the pediatric population. Their diagnosis is challenging because of the high cartilaginous component of the growing elbow, requiring a high level of clinical suspicion especially in the case of small osteochondral or chondral fragments. The literature on capitellar shear fractures is mainly represented by case reports, which provides a patchy view of the topic. For this reason, we aimed to draw a narrative review presenting the available management strategies and their outcomes, and present two cases treated in our institution.